A Meta-Analysis of Non-Repetitive Reading Fluency Interventions for Students With Reading Difficulties. (April 2021) - Zimmermann, Leah M.; Reed, Deborah K.; Aloe, Ariel M.
This meta-analytic review investigated non-repetitive reading fluency interventions for K-12 students with reading difficulties. Eight studies met inclusion criteria. The approaches were distinguished by their intervention structures; student groupings; and text difficulty, length, and genre. The overall multivariate weighted average standardized mean difference with robust variance yielded an improvement of less than 0.2 SD ( d = 0.176) for non-repetitive reading fluency interventions, but results were positive and statistically significant. The moderator analysis revealed that the effect on comprehension outcomes ( d = 0.239) was slightly larger than fluency outcomes ( d = 0.105), but differences between the magnitude of the two outcomes were not statistically significant. Moreover, there was no indication of concern for publication bias. Studies comparing repeated reading and non-repetitive reading fluency interventions produced reading outcomes similar in magnitude, with no significant differences. Results indicated that non-repetitive reading fluency instruction may be a feasible approach for students with reading difficulties.